Tranformasi Stilistika Alternative Universe dan Kontribusinya terhadap Literasi Bahasa Masa Depan - Raudlatul Jannah; Zamzani Zamzani; Albaburrahim Albaburrahim (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The emergence of new forms of literary works that utilize digital technology, such as Alternative Universe (AU) literature, has made literature relevant to the generation that grew up with social media and digital devices. This format offers a more visual and interactive reading experience, but perceptions of AU are still often compared to conventional literary works. The purpose of this study is to examine stylistic transformations in AU literature and their role in future language literacy. This study is a qualitative descriptive research using quotations from AU literary texts as data. The data analysis technique employed is a stylistic analysis approach, with the research process comprising data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that Alternative Universe literature has transformed Indonesian literature through four stylistic aspects: a shift in diction from formal-poetic to contemporary digital language, simplification of sentence structure and the dominance of mixed Indonesian-English code-switching, the explicit use of visual imagery through photos of idol characters, and the minimization of figurative language. AU significantly contributes to literacy through linguistic innovation (new vocabulary, abbreviations, acronyms), the democratization of digital literacy, and the development of multimodal literacy. AU literature shapes the future of the Indonesian language to be more complex with multiple registers and adaptive to technological developments.